Livias Bauten in Rom: Zur Rolle der Kaiserin im augusteischen Bauprogramm - Bolder-Boos, Marion (Römische Mitteilungen, 2024)
Several public buildings in the city of Rome and its immediate environs are associated with the empress Livia, who officially commissioned their construction or renovation: most notable is the Porticus Liviae. While her building activity has often been cited as part of the official Augustan construction programme, emphasising her role as ideal Roman matrona, Livia’s benefactions have never been properly investigated in their social and historical context. The present paper seeks to remedy this by placing Livia’s buildings into the wider field of female building activity in late Republican and Augustan times, thereby offering a new interpretation of her role in Augustus’ programme.